2014
DOI: 10.1590/0103-0582201432214613
|View full text |Cite
|
Sign up to set email alerts
|

Intake of protein, calcium and sodium in public child day care centers

Abstract: OBJECTIVE:To assess calcium, protein and sodium intake, of children that attend public day-care centers and to compare it with the recommended one. METHODS:Cross-sectional descriptive study in seven public day care centers of São Paulo city, Southeast Brazil, which enrolled 366 children between 12 and 36 months of age. The data collection occurred between September and December 2010. Each day care center was evaluated for three non-consecutive days, totaling 42 days and 210 meals. Dietary intake was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
5
0
7
Order By: Relevance
“…Different results were found by Longo-Silva et. Al 12 and Menezes and Osório 13 , who obtained energy values lower than recommendations.…”
Section: Discussionmentioning
confidence: 89%
“…Different results were found by Longo-Silva et. Al 12 and Menezes and Osório 13 , who obtained energy values lower than recommendations.…”
Section: Discussionmentioning
confidence: 89%
“…Uush [ 10 ] observed that 1–3-year-old Mongolian children consumed 39 % less Ca in their DFRs than the recommended value. The deficit of Ca was also observed in the diets of Indian and Brazilian children [ 11 , 12 ]. Low supply of Ca combined with low supply of vitamin D may cause disordered Ca homeostasis and irregular bone development [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ao analisar a quantidade de sódio oferecida por refeição, observa-se que 100% dos almoços e 60% dos jantares ultrapassaram o máximo de 400mg de sódio que seriam permitidos no fornecimento de uma única refeição (Tabela 2). Resultado similar foi encontrado para escolares, por Weber e Morais 15 , e para crianças que frequentam creches públicas, por Longo-Silva et al 16 .…”
Section: Discussionunclassified